COVID-19: guidance on palliative care from a European Respiratory Society international task force. Issue 3 (3rd September 2020) - Janssen, Daisy J.A.; Ekström, Magnus; Currow, David C.; Johnson, Miriam J.; Maddocks, Matthew; Simonds, Anita K.; Tonia, Thomy; Marsaa, Kristoffer
Background: Many people are dying from coronavirus disease 2019 (COVID-19), but consensus guidance on palliative care in COVID-19 is lacking. This new life-threatening disease has put healthcare systems under pressure, with the increased need of palliative care provided to many patients by clinicians who have limited prior experience in this field. Therefore, we aimed to make consensus recommendations for palliative care for patients with COVID-19 using the Convergence of Opinion on Recommendations and Evidence (CORE) process. Methods: We invited 90 international experts to complete an online survey including stating their agreement, or not, with 14 potential recommendations. At least 70% agreement on directionality was needed to provide consensus recommendations. If consensus was not achieved on the first round, a second round was conducted. Results: 68 (75.6%) experts responded in the first round. Most participants were experts in palliative care, respiratory medicine or critical care medicine. In the first round, consensus was achieved on 13 recommendations based upon indirect evidence and clinical experience. In the second round, 58 (85.3%) out of 68 of the first-round experts responded, resulting in consensus for the 14th recommendation. Conclusion: This multi-national task force provides consensus recommendations for palliative care for patients with COVID-19 concerning: advance care planning; (pharmacological) palliative treatment of breathlessness; clinician–patient communication; remote clinician–family communication; palliative care involvement in patients with serious COVID-19; spiritual care; psychosocial care; and bereavement care. Future studies are needed to generate empirical evidence for these recommendations. This multi-national task force provides consensus recommendations for palliative care for patients with COVID-19 https://bit.ly/31X83oZ